Representation of Racism in the Film “Good Hair: Perceptions of Racism” - Syafiqah, Kholifatus; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2024)
Racism is differentiated by the majority in the treatment of minorities on purpose based on inequality in skin color, race, race, even physical origin, and appearance that is thought to restrict and prohibit the rights and freedoms of a person. The research aims to describe the application of John Fiske's theory to analyze the forms of racial discrimination in this short film by approach to reality, representation, and ideology. Qualitative study methods of descriptive media text analysis examine three approaches to John Fiske's semiotics analysis. The results of this study suggest that the application of John Fiske's theory of discussing racism's representation in this short film lies in the visible levels of reality based on the codes of appearance, expression, and gestures. The representational level is indicated on the camera code. In contrast, ideology levels are indicated by the results of a level of reality and representation of the attitudes and dialogues of certain characters that reflect the behavior of racism. The racism reflected in this short film is a restriction on black people's rights and freedom to express themselves through their hairstyle. And the white people feel so superior, and all the standards and policies that exist should conform to their culture.